ESTIMATED BREEDING VALUES OF SERVICING BULLS OF THE HOLSTEIN BLACK-AND-WHITE BREED BY QUALITY OF OFFSPRING USING THE BLUP METHOD - Zhumanov Kanat Zheksembekovich; Karymsakov Talgat Nikolaevich; Kineev Marat Aidarovich; Baimukanov Aidar Dastanbekuly (Academic Journal of Physical and Chemical Sciences, 2020)
The aim of the research was to estimate the breeding value of the servicing bulls of the Holstein black-and-white breed according to the optimized equation of the mixed BLUP model. Within a comparative aspect, the estimation results of bulls calculated using the BLUP methodology are presented. As an object of the research, information was used on first-calf heifers (daughters of the evaluated bulls), who lactated in breeding herds of the Holstein cattle of the Republic of Kazakhstan in 2016-2017. The source was the official information analytical system (IAS) of livestock breeding of the Republic of Kazakhstan. The analysis of information on the dairy productivity of the cows-daughters of the estimated bulls was performed according to the indicators of the milk yield, the contents of fat and protein in milk, the milk fat and protein yield for 305 days of lactation and the study period. To compare the obtained results, the average values of breeding value indices, the reliability of their assessment, and the rank correlation coefficients were calculated.